Lahar paraisong abo - Chionglo, Mel; Lee, Ricardo (Star Cinema Production., 1996)
Filmed entirely in the devastated areas in Pampanga, It tells the story of entire barrio's dtruggle for survival and dignity after it is struck by the destructive volcanic miudflow known as Lahar.